Comparative approach to the revealed features of guardianship forminors in the Republic of Belarus and the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
This article is analytical in nature and reflects the basic requirements of codified sources of the Republic of Belarusand the Republic of Kazakhstan to the order of placement of minors left of parental care to guardianship.In order tostudy the institution of guardianship for minors and improvement of the order of its legal regulation in the Republic ofBelarus in the study institution is analyzed in the following aspects: setting goals; the competent authorities; the placeof establishment; the establishment period; persons over whom guardianship is established; the selection criteria forguardians; the requirements for the guardians; multiplicity of minors and guardians; the procedure of the establishmentof the guardianship and the appointment of a guardians; gratuitous fulfillment of guardianship duties.Key words: placement to the guardianship; orphaned children and children left of parental care; guardians.